A Colonial Tentweb Orbweaver Cyrtophora citricola - Lionel A. Stange (EDIS, 2013)
Few species of spiders can be considered truly social, but a greater number of species, particularly web-building spiders, live in close proximity to one another. One species which has become highly successful through a lifestyle of colonial aggregation is the orbweaver Cyrtophora citricola Forskål. This 6-page fact sheet was written by Lionel A. Stange, and published by the UF Department of Entomology and Nematology, October 2012.